THE EXPERIENCE OF LITERARY-DRAMATIC RADIO BROADCASTINGS IN THE CONTEXT OF CREATION OF MATERIALS FOR MODERN INFORMATION AND COLLOQUIAL RADIO STATIONS - Sheveleva, E.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2017)
The article analyzes the way of formation and development of the means of artistic expression of radio, examines the specifics of their impact on the listener. The last large-scale study of this topic was made by A.A. Sheryl. The results are reflected in the number of essays named “The Audio - culture of the XXth century”, which were published in 2004. The modern way of broadcasting differs from the one we had in 2000s. New trends, such as convergence, focus on social media sources, have radically changed the traditional genres and forms of the media industry sector. For the sake of efficiency less attention is paid to the proper, unique sounding of the radio and this, in turn, negatively affects the quality of the materials going on the air.